2022
DOI: 10.3390/pr10061123
|View full text |Cite
|
Sign up to set email alerts
|

The Seal Performance of Compliant Foil Gas Seal Based on Multi-Scale Analysis

Abstract: Compliant foil gas seal is a non-contact and high-efficiency sealing technology. The dynamic performance of compliant foil gas seal with different structure parameters was analyzed in this paper. These parameters include the seal diameter, gas film thickness and the ratio of groove. Compared with the rigid film, the advantage of compliant film is analyzed. The stability performance and dynamic performance with the different structures are obtained. The results show that the larger diameter is a disadvantage fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Chen Shuda [100] used a combination of the finite element method and a Newton-Raphson iterative method for the sealing of high-pressure cylinders of steam turbines, using high-temperature and high-pressure water vapor as the sealing medium, to analyze the effects of arch foil thickness, eccentricity, etc., on the static characteristics of the compliant foil seal. Wang Xueliang et al [101] analyzed the sealing characteristics of compliant foil cylindrical gas film seals with different surface roughness values, and tested the influence of surface roughness values on the start-stop cycling performance of high-speed compliant foil seals, and the results showed that the improvement of interfacial surface properties can effectively a enuate the hysteresis effect of the seal. Sun Junfeng et al [102] proposed a new compliant support foil gas film seal structure that can absorb vibration and reduce thermal deformation of the rotor system, as shown in Figure 21.…”
Section: Compliant Foil Cylindrical Gas Film Seal Structuresmentioning
confidence: 99%
“…Chen Shuda [100] used a combination of the finite element method and a Newton-Raphson iterative method for the sealing of high-pressure cylinders of steam turbines, using high-temperature and high-pressure water vapor as the sealing medium, to analyze the effects of arch foil thickness, eccentricity, etc., on the static characteristics of the compliant foil seal. Wang Xueliang et al [101] analyzed the sealing characteristics of compliant foil cylindrical gas film seals with different surface roughness values, and tested the influence of surface roughness values on the start-stop cycling performance of high-speed compliant foil seals, and the results showed that the improvement of interfacial surface properties can effectively a enuate the hysteresis effect of the seal. Sun Junfeng et al [102] proposed a new compliant support foil gas film seal structure that can absorb vibration and reduce thermal deformation of the rotor system, as shown in Figure 21.…”
Section: Compliant Foil Cylindrical Gas Film Seal Structuresmentioning
confidence: 99%
“…Based on the fluid-solid coupling analysis method, Sun et al [19] explored the static characteristics of compliant foil gas seal and the mechanical properties of its supporting structures under different operating parameters. Wang et al [20,21] studied the effects of structural and operating parameters on steady-state sealing performance and gas film dynamic characteristics of compliant foil gas seal.…”
Section: Introductionmentioning
confidence: 99%